Respuesta :
7x + 4 = x - 2 -- (1)
To rewrite the equation above as a system, we simply let (1) be equal to y, i.e.
7x + 4 = x - 2 = y -- (2)
Recall from the rule of transitivity: If a = b = c, then this implies that a = c & b = c. From this, we have (2) to be expressed as
y = 7x + 4 -- (i)
y = x - 2 -- (ii)
Note: (i) & (ii) are both regarded as a system of linear equation which can be evaluated simultaneously.
To rewrite the equation above as a system, we simply let (1) be equal to y, i.e.
7x + 4 = x - 2 = y -- (2)
Recall from the rule of transitivity: If a = b = c, then this implies that a = c & b = c. From this, we have (2) to be expressed as
y = 7x + 4 -- (i)
y = x - 2 -- (ii)
Note: (i) & (ii) are both regarded as a system of linear equation which can be evaluated simultaneously.
Answer:
C
The next questions answer is -1
Step-by-step explanation:
For edge:)